Human antibodies neutralizing the alpha-latrotoxin of the European black widow - Ruschig, Maximilian; Nerlich, Jana; Becker, Marlies; Meier, Doris; Polten, Saskia; Cervantes-Luevano, Karla; Kuhn, Philipp; Licea-Navarro, Alexei Fedorovish; Hallermann, Stefan; Dübel, Stefan; Schubert, Maren; Brown, Jeffrey; et al. (Frontiers in Immunology, 2024)
Poisoning by widow-spider (genus Latrodectus) bites occurs worldwide. The illness, termed latrodectism, can cause severe and persistent pain and can lead to muscle rigidity, respiratory complications, and cardiac problems. It is a global health challenge especially in developing countries. Equine serum-derived polyclonal anti-sera are commercially available as a medication for patients with latrodectism, but the use of sera imposes potential inherent risks related to its animal origin. The treatment may cause allergic reactions in humans (serum sickness), including anaphylactic shock. Furthermore, equine-derived antivenom is observed to have batch-to-batch variability and poor specificity, as it is always an undefined mix of antibodies. Because latrodectism can be extremely painful but is rarely fatal, the use of antivenom is controversial and only a small fraction of patients is treated. In this work, recombinant human antibodies were selected against alpha-latrotoxin of the European black widow (Latrodectus tredecimguttatus) by phage display from a naïve antibody gene library. Alpha-Latrotoxin (α-LTX) binding scFv were recloned and produced as fully human IgG. A novel alamarBlue assay for venom neutralization was developed and used to select neutralizing IgGs. The human antibodies showed in vitro neutralization efficacy both as single antibodies and antibody combinations. This was also confirmed by electrophysiological measurements of neuronal activity in cell culture. The best neutralizing antibodies showed nanomolar affinities. Antibody MRU44–4-A1 showed outstanding neutralization efficacy and affinity to L. tredecimguttatus α-LTX. Interestingly, only two of the neutralizing antibodies showed cross-neutralization of the venom of the Southern black widow (Latrodectus mactans). This was unexpected, because in the current literature the alpha-latrotoxins are described as highly conserved. The here-engineered antibodies are candidates for future development as potential therapeutics and diagnostic tools, as they for the first time would provide unlimited supply of a chemically completely defined drug of constant quality and efficacy, which is also made without the use of animals.